Developing Crossword Puzzle As English Learning Media Media To Teach Vocabulary At Madrasah Aliyah Al Khoiriyah Gondanglegi - Khasanah, Alfinindya Faizah Afifatul; Rofi’ah, Siti; Mubarok, Tyas Alhim (Jurnal Ilmiah Mandala Education (JIME), 2023)
In order to learn and teach effectively, students need to have a comprehensive knowledge of the English language and understand its meaning. Students must be able to understand language both orally and in writing if they have mastery of vocabulary. The purpose of this writing is to find out whether the application of the media could develop English learning media to teach vocabulary at Madrasah Aliyah Al Khoiriyah Gondanglegi. The instruments used was the Research and Development (R&D) media with 20 students as a trial in applying this method. The results of this study are based on the results of the average percentage of the validation sheet by 2 crossword puzzle learning media experts of 94.8% and is included in the very valid category. Thus, the developed crossword puzzle learning media can be used at Madrasah Aliyah Al Khoiriyah Gondanglegi. Based on the results of the distribution of questionnaires given by students and English teachers to find out the responses of students and teachers to crossword learning media. The percentage of responses given by students is very valid at 81%, and teacher responses with a very valid percentage are 93.3%. Thus, most students and teachers responded in a very valid category to the development of crossword puzzle learning media at Madrasah Aliyah Al Khoiriyah.